Strategic Communication of Local Government - Aries Aries (Program Studi Ilmu Komunikasi Universitas Serang Raya, 2024)
The implementation of local government affairs in the field of communication is still limited to organizing routine activities that only focus on message production and message dissemination - not focused on communication activities that have a strategic impact on the local government institution itself. The implementation of local government communication affairs should ideally focus on efforts to align programs/activities (planning) with actions (implementation of activities) of each component of regional apparatus to achieve organizational goals and objectives. So that each work unit and regional apparatus has the same direction to work together to carry out various activities that contribute to the achievement of goals and objectives set in the strategic plan. Local government strategic communication in this study is a series of planned activities on information management and practical communication that is prepared based on government administration that provides prospects for benefits for local government institutions; realizing effective internal communication to achieve organizational goals and objectives; building institutional image and reputation; and optimizing institutional communication with the community and stakeholders.